REAKSI PASAR MODAL INDONESIA TERHADAP PENGUMUMAN RESHUFFLE KABINET INDONESIA MAJU JILID I DAN II - Made Aditya Budastra; Lukman Effendy; Robith Hudaya; I Ketut Budastra (Jurnal Bisnis Terapan, 2022)
This study aims to see whether or not there is a market reaction when information about the Indonesian Maju Cabinet reshuffle volumes I and II is circulated in the Indonesian capital market. This study use event study methods. Data analysis was carried out through different tests. The sample used is financial sector in Indonesia Stock Exchange. The variables used to measure market reaction is average abnormal return (AAR) and average trading volume activity (ATVA). The results of this study found that there is no significant difference in AAR and ATVA between before and after the event, both in the Indonesia Maju Cabinet reshuffle event Volume I and Volume II, which indicates that the two events are not contain information that is sufficiently informative to influence the market.